Atmospheric degradation of 3-ethoxy-1-propanol by reactions with Cl, OH and NO3. (October 2021) - Aranda, Inmaculada; Salgado, Sagrario; Martín, Pilar; Villanueva, Florentina; Martínez, Ernesto; Cabañas, Beatriz
Abstract: An experimental kinetic and mechanistic study of the reactions of 3-ethoxy-1-propanol (CH3 CH2 OCH2 CH2 CH2 OH) with Cl atoms and OH and NO3 radicals has been carried out at room temperature and atmospheric pressure. FTIR (Fourier Transform Infrared Spectroscopy) and GC-MS (Gas Chromatography/Mass Spectrometry) were used as detection techniques. The rate coefficients were measured with a relative method (units cm 3 molecule −1 s −1 ): (3.46 ± 0.22) × 10 −10, (3.48 ± 0.19) × 10 −11 and (1.08 ± 0.07) × 10 −14 for Cl, OH and NO3 reactions, respectively. Qualitative and quantitative products analysis was carried out and formaldehyde, ethyl formate, ethyl 3-hydroxypropanoate and nitrated compounds were positively identified. A reaction mechanism has been proposed which involves attack by the oxidant at the methylene group in the α-position to an oxygen atom of the ether or alcohol groups, followed by the subsequent reactions of the resulting radicals. The tropospheric reactivity of 3-ethoxy-1-propanol (3E1P) has been compared with the reactivity of other hydroxy ethers to extend our knowledge of this type of compound. The atmospheric implications for 3E1P have been established by estimating parameters such as lifetimes, global warming potential (GWP) and the Photochemical Ozone Creation Potential (POCPE ). According to the calculated tropospheric lifetimes, the dominant loss process of 3E1P is its daytime reaction with the OH radical and this has an impact on a local scale. Graphical abstract: Image 1 Highlights: First kinetic data for the reaction of 3E1P with Cl atoms and NO3 radicals. High reactivity of hydroxyethers due to the presence of alcohol and ether groups. Mechanism proposed with the formation of carbonylic and multifunctional products. Short atmospheric lifetime with OH radicals, what implies a local impact. Importance of the products formed and its POCP.